Synthesis of transition metal sulfide and reduced graphene oxide hybrids as efficient electrocatalysts for oxygen evolution reactions. Issue 9 (26th September 2018) - Hong, Yu-Rim; Mhin, Sungwook; Kwon, Jiseok; Han, Won-Sik; Song, Taeseup; Han, HyukSu
Abstract : The development of electrochemical devices for renewable energy depends to a large extent on fundamental improvements in catalysts for oxygen evolution reactions (OERs). OER activity of transition metal sulfides (TMSs) can be improved by compositing with highly conductive supports possessing a high surface-to-volume ratio, such as reduced graphene oxide (rGO). Herein we report on the relationship between synthetic conditions and the OER catalytic properties of TMSs and rGO (TMS–rGO) hybrids. Starting materials, reaction temperature and reaction time were controlled to synergistically boost the OER catalytic activity of TMS–rGO hybrids. Our results showed that (i) compared with sulfides, hydroxides are favourable as starting materials to produce the desired TMS–rGO hybrid nanostructure and (ii) high reaction temperatures and longer reaction times can increase physico-chemical interaction between TMSs and rGO supports, resulting in highly efficient OER catalytic activity.